Parameters for Applying the Brainstem Auditory Evoked Potential with Speech Stimulus: Systematic Review - Gabriel, Luísa Bello; Vernier, Luíza Silva; Ferreira, Maria Inês Dornelles da Costa; Silveira, Adriana Laybauer; Machado, Márcia Salgado (International Archives of Otorhinolaryngology, 2018)
Introduction Studies using the Brainstem Auditory Evoked Potential with speech stimulus are increasing in Brazil, and there are divergences between the methodologies used for testing.Objectives To analyze the parameters used in the study of the Brainstem Auditory Evoked Potentials with speech stimulus.Data Synthesis The survey was performed using electronic databases. The search strategy was as follows: “Evoked potentials, auditory” OR “Brain stem” OR “Evoked potentials, auditory, brain stem” AND “Speech.” The survey was performed from June to July of 2016. The criteria used for including articles in this study were: being written in Portuguese, English or Spanish; presenting the description of the testing parameters and the description of the sample. In the databases selected, 2,384 articles were found, and 43 articles met all of the inclusion criteria. The predominance of the following parameters was observed to achieve the potential during study: stimulation with the syllable /da/; monaural presentation with greater use of the right ear; intensity of 80 dB SPL; vertical placement of electrodes; use of in-ear headphones; patient seated, distracted in awake state; alternating polarity; use of speech synthesizer software for the elaboration of stimuli; presentation rate of 10.9/s; and sampling rate of 20 kHz.Conclusions The theme addressed in this systematic review is relatively recent. However, the results are significant enough to encourage the use of the procedure in clinical practice and advise clinicians about the most used procedures in each parameter.
Keywords: evoked potentials, auditory; electrophysiology; speech